The Role of Village Government in Improving Welfare Through Food Assistance in Cinta Rakyat Village: Peran Pemerintahan Desa Dalam Meningkatkan Kesejahteraan Melalui Bantuan Pangan di Desa Cinta Rakyat - Fatiya Nur Rahma; Julia Ivanna (SOSIOEDUKASI, 2024)
In realizing just and prosperous social welfare, as well as in improving the community's economy through Non-Cash Food Assistance (BPNT) in Cinta Rakyat Village, the role of the village government is needed to ensure the welfare of its people. The aim of this research is to determine the role of the Cinta Rakyat Village Government in distributing food aid to improve community welfare. The research method used is a qualitative method and a descriptive approach, where this research was carried out using interview techniques and sources were found directly in the field. The results of this research are that the role of government in Cinta Rakyat Village is quite good in distributing food aid.